The impact of the innovative performance of the country on its economic development - Belanova, Katarina (Mednarodno inovativno poslovanje, 2023)
Innovations are a way how to improve the quality of life, support sustainable solutions, attract talent, increase competitiveness, or increase GDP. The aim of the article is to verify the dependence of GDP per capita on the innovation performance of the country by the regression and correlation analysis. The secondary data contained in the European Innovation Scoreboard 2023 (for the innovation performance) and the related EUROSTAT datasets within the EU countries (for the level of countries`wealth) were used. According to the results, there is a significant interdependence between innovation performance of the country and its wealth. There have not been many empirical studies realized in Slovakia yet. The author herself dealt with the evaluation of the innovation performance of the SR in her previous studies. Her motivation is to use quantitative method to analyse this issue in a more detail.
Keywords: Bruto domači proizvod; economic development; gospodarski razvoj; innovations; inovacije; regresijska analiza; regression analysis